2005
DOI: 10.1002/jcb.20525
|View full text |Cite|
|
Sign up to set email alerts
|

PTEN enters the nucleus by diffusion

Abstract: Despite much evidence for phosphatidylinositol phosphate (PIP)-triggered signaling pathways in the nucleus, there is little understanding of how the levels and activities of these proteins are regulated. As a first step to elucidating this problem, we determined whether phosphatase and tensin homolog deleted on chromosome 10 (PTEN) enters the nucleus by passive diffusion or active transport. We expressed various PTEN fusion proteins in tsBN2, HeLa, LNCaP, and U87MG cells and determined that the largest PTEN fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 65 publications
2
84
0
4
Order By: Relevance
“…However, another group has recently reported that PTEN's nuclear entry is mediated by passive diffusion (21). To further confirm our conclusion, the present study examined the effect of siRNAmediated silencing of MVP on PTEN subcellular localization.…”
Section: Discussionsupporting
confidence: 63%
“…However, another group has recently reported that PTEN's nuclear entry is mediated by passive diffusion (21). To further confirm our conclusion, the present study examined the effect of siRNAmediated silencing of MVP on PTEN subcellular localization.…”
Section: Discussionsupporting
confidence: 63%
“…Interestingly, PTEN was found in this study to interact with importin a and b proteins, although such interaction was also observed in the NLS-like mutants that displayed defective nuclear accumulation. A second model of PTEN nuclear entry has been proposed by Liu et al 12 Using PTEN fusion proteins of variable size, the authors of this study noticed that large PTEN fusion proteins (4100 kDa) did not show nuclear localization, whereas PTEN alone (47 kDa) or a GFP-PTEN fusion protein (74 kDa) were present in both the cytoplasm and the nucleus. Also, nuclear localization of GFP-PTEN was not altered in tsBN2 cells, which show defective Ran-dependent nuclear transport at a nonpermissive temperature.…”
Section: Molecular Mechanisms Of Pten Nuclear Accumulationmentioning
confidence: 76%
“…However, the N-terminal region of PTEN, when fused to chicken PK, did not facilitate the nuclear accumulation of this protein. Also of interest, Liu et al 12 found a fast mobility of GFP-PTEN into the nucleus, whereas in the cytoplasm the movement of GFP-PTEN was much more restricted, suggesting the tethering of PTEN to cytoplasmic structures which could prevent nuclear translocation. A third model to explain the nuclear accumulation of PTEN has been proposed more recently by us.…”
Section: Molecular Mechanisms Of Pten Nuclear Accumulationmentioning
confidence: 99%
See 1 more Smart Citation
“…32 In the present study, we observed the decreased expressions of cyclin D3, CDK4 and PCNA, and increased expressions of cell cycle inhibitor p27 and p21 in the PTEN delivery lungs (Figure 4). Several recent studies 33,34 have reported that PTEN entered into nucleus through passive diffusion is prominent in the G 0 /G 1 segment of cell cycle. According to Freeman et al 26 and Su et al 35 p53 in the complex with PTEN inhibits cell cycle through increasing the CDK inhibitors such as p21 and p27.…”
Section: Discussionmentioning
confidence: 99%